Preliminary evaluation of the role of activated carbon in soil/water remediation - Viktor Mukhin; Nicolai Koroleov; Valentina Mednyak; Tudor Lupascu; Elena Culighin (Romanian Journal of Ecology & Environmental Chemistry, 2021)
This paper presents brief scientific information concerning the role of activated carbons (AC) in solving economic and ecological problems in our society. Data concerning synthesis and adsorption of new activated carbons, used for soil remediation and wastewater treatment are depicted. The findings of investigations aimed to compare the structure parameters and adsorption capacities of the newly obtained native activated carbons in comparison with several activated carbon marks known in the world are explained. It has been shown that currently synthesized activated carbons are competitive with foreign marks.